Superior haplotypes for haplotype-based breeding for drought tolerance in pigeonpea (Cajanus cajan L.) - Sinha, Pallavi; Singh, Vikas K.; Saxena, Rachit K.; Khan, Aamir W.; Abbai, Ragavendran; Chitikineni, Annapurna; Desai, Aarthi; Molla, Johiruddin; Upadhyaya, Hari D.; Kumar, Arvind; Varshney, Rajeev K. (Wiley, 2020)
Haplotype‐based breeding, a recent promising breeding approach to develop tailor‐made crop varieties, deals with identification of superior haplotypes and their deployment in breeding programmes. In this context, whole genome re‐sequencing data of 292 genotypes from pigeonpea reference set were mined to identify the superior haplotypes for 10 drought‐responsive candidate genes. A total of 83, 132 and 60 haplotypes were identified in breeding lines, landraces and wild species, respectively. Candidate gene‐based association analysis of these 10 genes on a subset of 137 accessions of the pigeonpea reference set revealed 23 strong marker‐trait associations (MTAs) in five genes influencing seven drought‐responsive component traits. Haplo‐pheno analysis for the strongly associated genes resulted in the identification of most promising haplotypes for three genes regulating five component drought traits. The haplotype C. cajan_23080‐H2 for plant weight (PW), fresh weight (FW) and turgid weight (TW), the haplotype C. cajan_30211‐H6 for PW, FW, TW and dry weight (DW), the haplotype C. cajan_26230‐H11 for FW and DW and the haplotype C. cajan_26230‐H5 for relative water content (RWC) were identified as superior haplotypes under drought stress condition. Furthermore, 17 accessions containing superior haplotypes for three drought‐responsive genes were identified. The identified superior haplotypes and the accessions carrying these superior haplotypes will be very useful for deploying haplotype‐based breeding to develop next‐generation tailor‐made better drought‐responsive pigeonpea cultivars.